Cytokine–Ion Channel Interactions in Pulmonary Inflammation - Hamacher, Jürg; Hadizamani, Yalda; Borgmann, Michèle; Mohaupt, Markus; Männel, Daniela Narcissa; Moehrlen, Ueli; Lucas, Rudolf; Stammberger, Uz (Frontiers in Immunology, 2018)
The lungs conceptually represent a sponge that is interposed in series in the bodies’ systemic circulation to take up oxygen and eliminate carbon dioxide. As such, it matches the huge surface areas of the alveolar epithelium to the pulmonary blood capillaries. The lung’s constant exposure to the exterior necessitates a competent immune system, as evidenced by the association of clinical immunodeficiencies with pulmonary infections. From the in utero- to the postnatal and adult situation there is an inherent vital need to manage alveolar fluid re-absorption, be it postnatally, or in case of hydrostatic or permeability oedema. Whereas a wealth of literature exists on the physiological basis of fluid and solute re-absorption by ion channels and water pores, only sparse knowledge is available so far on pathological situations, such as in microbial infection, acute lung injury or ARDS, and in the pulmonary re-implantation response in transplanted lungs. The aim of this review is to discuss alveolar liquid clearance in a selection of lung injury models, thereby especially focusing on cytokines and mediators that modulate ion channels. Inflammation is characterized by complex and probably time-dependent co-signalling, interactions between the involved cell types, as well as by cell demise and barrier dysfunction, which may not uniquely determine a clinical picture. This review therefore aims to give integrative thoughts and wants to foster the unravelling of unmet needs in future research.